An Exploratory Study of Police Officers: Low Compassion Satisfaction and Compassion Fatigue - Grant, Heath Blair; Lavery, Cathryn F.; Decarlo, John (Frontiers in Psychology, 2019)
Aim: This exploratory study documents the incidence of compassion fatigue amongst a sample of urban officers. Results of this trial study incorporate new aspects of recovery capital and its impact on law enforcement officers. Specific recommendations for treatment and future research are presented based on these findings. Conclusion: Very low levels of compassion fatigue were found in the sampled police officers in comparison to what would be expected given what we know about the general non-law enforcement population. Where compassion fatigue was found in the sampled police personnel, it was significantly correlated to the level of compassion satisfaction. A potential cause for concern is that the incidence of satisfactory compassion satisfaction was very low in the sample (in the bottom quartile compared to the general population). If unaddressed, this suggests a possibility of widespread burnout in the future given the importance of compassion satisfaction as recovery capital in mitigating burnout and compassion fatigue in policing.